Adivasi images, Adivasi voices. the resonance of the Eickstedt collection - Carrin, Marine (Modern Asian Studies)
his article analyses how past and contemporary Adivasi voices are expressed in colonial photographs, and how they have$1 (Band continue to$1 (Bboth enable and restrict speaking through visual representation. It examines the collection of the German anthropologist Egon von Eickstedt, who in the 1920s took about 12,000 photographic images and 2,000 objects from Adivasi communities in India, Ceylon, and Burma. As a racial anthropologist he defined and framed the photos and created the collection according to his own preconceptions. The photographs, embedded in a colonial context and an increasingly racial/racist German anthropology, reveal very asymmetric power relations. Yet, the voice of the Adivasi is not completely suppressed, as the photographed people are not mere objects, but find various ways of expressing sentiments in the photographs. Ninety years on, the images and objects have lost none of their ambiguity. They continue to resonate when newly arranged and criticized in the permanent exhibition of a German museum, as well as when curated at the Museum of Voice of the Adivasi Academy in Gujarat.- Reproduced s
Keywords: Santal, Central Indian, Inigeneity, Indigenous knowledge, Politics of representation